Risk of pancreatic cancer associated with family history of cancer and other medical conditions by accounting for smoking among relatives. (10th January 2018) - Molina-Montes, E; Gomez-Rubio, P; Márquez, M; Rava, M; Löhr, M; Michalski, C W; Molero, X; Farré, A; Perea, J; Greenhalf, W; Ilzarbe, L; O'Rorke, M; et al.
Abstract: Background: Family history (FH) of pancreatic cancer (PC) has been associated with an increased risk of PC, but little is known regarding the role of inherited/environmental factors or that of FH of other comorbidities in PC risk. We aimed to address these issues using multiple methodological approaches. Methods: Case-control study including 1431 PC cases and 1090 controls and a reconstructed-cohort study ( N = 16 747) made up of their first-degree relatives (FDR). Logistic regression was used to evaluate PC risk associated with FH of cancer, diabetes, allergies, asthma, cystic fibrosis and chronic pancreatitis by relative type and number of affected relatives, by smoking status and other potential effect modifiers, and by tumour stage and location. Familial aggregation of cancer was assessed within the cohort using Cox proportional hazard regression. Results: FH of PC was associated with an increased PC risk [odds ratio (OR) = 2.68; 95% confidence interval (CI): 2.27-4.06] when compared with cancer-free FH, the risk being greater when ≥ 2 FDRs suffered PC (OR = 3.88; 95% CI: 2.96-9.73) and among current smokers (OR = 3.16; 95% CI: 2.56-5.78, interaction FHPC*smoking P- value = 0.04). PC cumulative risk by age 75 was 2.2% among FDRs of cases and 0.7% in those of controls [hazard ratio (HR) = 2.42; 95% CI: 2.16-2.71]. PC risk was significantly associated with FH of cancer (OR = 1.30; 95% CI: 1.13-1.54) and diabetes (OR = 1.24; 95% CI: 1.01-1.52), but not with FH of other diseases. Conclusions: The concordant findings using both approaches strengthen the notion that FH of cancer, PC or diabetes confers a higher PC risk. Smoking notably increases PC risk associated with FH of PC. Further evaluation of these associations should be undertaken to guide PC prevention strategies.